Research Progress of PROTAC-Degraded CDKs in the Treatment of Breast Cancer - Zhao K; Zhang J; Yang Z; Wang R; Shi Y; Ji Y; Zhang S; Liu M (Breast Cancer: Targets and Therapy)
Kexin Zhao,1 Jun Zhang,1 Zhe Yang,1 Rong Wang,1 Yuhuan Shi,1 Yanan Ji,1 Shengjun Zhang,2 Minli Liu1 1Yan’an Medical College of Yan’an University, Yan’an, People’s Republic of China; 2Department of General Surgery, Yan’an University Affiliated Hospital, Yan’an, People’s Republic of ChinaCorrespondence: Shengjun Zhang, Email zsj@yau.edu.cn Minli Liu, Email lml@yau.edu.cnAbstract: Breast cancer (BC) is the most common type of cancer among women worldwide. A large number of studies have found that the high expression or dysregulation of cyclin-dependent protein kinases (CDKs) is closely associated with breast cancer. For example, the CDK4/6-Rb axis is involved in the G1/S phase transition of the cell cycle and plays an important role in BC; CDK1 and its associated cyclin are commonly involved in mitotic progression, and increased expression of CDK1-associated cyclin has been observed in BC; loss of CDK12 significantly ameliorates triple-negative breast cancer. CDKs are one of the major families within the group of PROteolysis Targeting Chimeras (PROTACs)-degraded kinases. PROTAC is a potent technology for protein-targeted degradation, whose molecules consist of the ligand of the Protein of Interest (POI), the ligand of the E3 ubiquitin ligase (E3), and a Linker. After binding to POI, PROTAC can recruit E3 to ubiquitinate POI via ubiquitin-proteasome mediated degradation. In this review, we summarize relevant research results and review that PROTAC can effectively inhibit the proliferation of breast cancer cells by inducing ubiquitination of CDK1, CDK4/6, CDK9, CDK12/13 and their subsequent degradation by proteasomes, which is expected to be a novel approach for the treatment of breast cancer.Keywords: breast cancer, ubiquitin, PROTAC, CDKs